Identification of Copper-Induced Genes in the Marine Alga Ulva Compressa (Chlorophyta) - Moenne-Munoz, A; Dennett-Rios, G; Gonzalez-Figueroa, A (2011)
In order to identify genes/proteins involved in copper tolerance, the marine alga Ulva compressa was cultivated with 10 ?M copper for 3 days. The activities of antioxidant enzymes ascorbate peroxidase (AP), peroxiredoxin (PRX), thioredoxin (TRX), and glutathione-S-transferase (GST) and the level of lipoperoxides were determined in the alga cultivated with and without copper addition. Antioxidant enzyme activities and lipoperoxides level increased in response to copper excess, indicating that the alga was under oxidative stress. A cDNA library was prepared using U. compressa cultivated with 10 ?M copper for 3 days. A total of 3 × 10 4 clones were isolated and 480 clones were sequenced, resulting in 235 non-redundant ESTs, of which 104 encode proteins with known functions. Among them, we identified proteins involved in (1) antioxidant metabolism such as AP, PRX, TRX, GST, and metalothionein (MET), (2) signal transduction, such as calmodulin (CAM), (3) calcium-dependent protein kinase (CDPK) and nucleoside diphosphate kinase (NDK), (4) gene expression, (5) protein synthesis and degradation, and (6) chloroplast and mitochondria electron transport chains. Half of the identified proteins are potentially localized in organelles. The relative level of 18 genes, including those coding for AP, PRX, TRX, GST, MET, CAM, CDPK, and NDK were determined by quantitative RT-PCR in the alga cultivated with 10 ?M copper for 0 to 7 days. Transcript levels increased in response to copper stress and most of them reached a maximum at days 3 and 5. Thus, the selected genes are induced by copper stress and they are probably involved in copper acclimation and tolerance. © 2010 Springer Science+Business Media, LLC.